Evaluation of Physical Quality of Patchouli Oil (Pogostemon cablin Benth.) Body Butter Formulation - Nadia Isnaini; Khairan Khairan; Meutia Faradhilla; Elly Sufriadi; Binawati Ginting; Vicky Prajaputra; Friesca Erwan; Raihan Dara Lufika; Syaifullah Muhammad (Journal of Patchouli and Essential Oil Products, 2022)
Patchouli oil (Pogostemon cablin Benth.) has antioxidant and antibacterial activities that can be used as an active ingredient in cosmetic products, such as body butter. Body butter preparations have the highest oil content. Therefore, they usually have the shortest storage period because they can easily damage during the storage period. The study aimed to evaluate the physical quality of patchouli oil body butter formulation in an accelerated stability test process for seven cycles. The formula was tested for its physical stability by organoleptic test, homogeneity, pH, absorption, adhesion, and dispersibility. Preparation evaluation was carried out in each cycle and analyzed using Student's t-test. The evaluation result of body butter preparation showed no significant difference (p 0.05) in the preparation in each cycle. Therefore, it can be concluded that the body butter formulation of patchouli oil was stable during the storage period for ± six months.